Ship’s Course Changing Controller in Low Speed under Wind Conditions - Arianto, Sigit (INKOM Journal, 2012)
Maneuvering in harbor is considered as one of the most sophisticated and difficult maneuvers in ship’s operation. Much knowledge and experience are demanded to accomplish berthing. Automation of berthing is highly needed to meet the decrease of the number and aging of crew. In berthing, the environmental factor that affects ship the most is wind while current and wave affect the least. This wind effect is made worse because ship’s speed will be slowed down during the berthing process. Therefore in this part of research, effects of wind disturbance on marine vessels that are in the process of berthing in the harbor were analyzed by using a turning test. The influence of wind included in the process of designing a controller for the ship to keep and change its direction. Basically, for both types of controller, it is used Proportional Derivative (PD) controller type, only the coefficients for each controller have different parameters. A new algorithm for controller to change direction under the influence of winds is used in this study. The algorithm is based on several factors. The main thing is to make the same yaw rate, either when there is wind or no wind. Results from simulations show good performance when the ship changed direction or turn under the influence of wind. The result is almost equal to the control of PD when there is no wind.Keywords: PD Controller, Wind Influence, Automatic Berthing, Neural Networks Manuver di pelabuhan adalah salah satu manuver paling canggih dan sulit dalam pengoperasian kapal. Banyak pengetahuan dan pengalaman yang harus dimiliki untuk berlabuh dengan sukses. Otomasi berlabuh sangat diperlukan untuk memenuhi penurunan jumlah dan penuaan dari awak kapal. Dalam hal berlabuh, faktor lingkungan yang mempengaruhi manuver kapal yang paling kuat adalah angin sedangkan arus dan gelombang adalah paling sedikit. Efek angin ini menjadi lebih buruk karena kecepatan kapal akan melambat selama proses berlabuh.Oleh karena itu, pengaruh dari gangguan angin terhadap kapal laut yang sedang dalam proses berlabuh di pelabuhan telah dianalisa dengan menggunakan tes berputar (turning test). Pengaruh dari angin dimasukan dalam proses merancang kendali untuk kapal menjaga arahnya dan untuk merubah arahnya. Pada dasarnya, untuk kedua jenis kendali ini digunakan pengendali Proportional Derivative (PD), hanya koefisien untuk masing-masing parameter berbeda. Algoritma baru untuk system kendali untuk merubah arah di bawah pengaruh angin digunakan dalam penelitian ini. Algoritma ini didasarkan pada beberapa faktor. Yang paling utama adalah ingin membuat laju simpang (yaw) yang sama, baik ketika ada angin dengan tidak ada angin. Hasil dari simulasi menunjukan kinerja yang baik ketika kapal berganti arah atau berbelok di bawah pengaruh angin. Hasilnya hampir menyamai kendali PD ketika tidak ada angin.Kata kunci: Pengendali PD, Pengaruh Angin, Berlabuh Otomatis, Jaringan Syaraf Tiruan